Examining the effect of physical fields on the adhesive strength of protective epoxy composite coatings - Kashytskyi, Vitalii; Savchuk, Petro; Malets, Viktoria; Herasymiuk, Yuliia; Shchehlov, Serhii (Eastern-European Journal of Enterprise Technologies, 2017)
We examined and substantiated the effect of treating the compositions in the electromagnetic field and with ultrasound on the adhesive strength of epoxy composites that contain highly dispersed particles of ferro-, para- and diamagnetic nature. It was established experimentally that the optimal content of highly dispersed fillers is 6 mass fractions. The studies conducted confirm the prospects of using the treatment of compositions in physical fields for obtaining epoxy composite protective coatings. The given technology enables to ensure high adhesive strength (60–70 MPa) of bonds between a coating and a metal base, to increase the degree of structuring (G=99.7 %) and to reduce by 65 % internal stresses in coatings. We achieved an increase in the number of physical-chemical bonds between an epoxy polymer binder and the surface of highly dispersed particles by increasing the mobility of segments of macromolecules and improving the interaction between components of the system under the influence of external physical fields. By using the electron microscopy method, we registered a uniform distribution of ferro- and paramagnetic particles in epoxy composites after treating the compositions in the electromagnetic field. This occurs due to the orientation of the dipole segments of macromolecules in a force field and the uniform distribution of chemical bonds in the structure of epoxy composite. The received epoxy composite coatings with highly dispersed powders after treating the compositions in the physical field are characterized by defect-free structure. Epoxy composite coatings could be used as wear- and corrosion resistant coatings for parts of machines and mechanisms in automotive and instrument-making industries, as well as in the oil and gas sector. Such parts can operate under conditions of temperature gradient, mechanical stresses, deformations and aggressive impacts.